(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
A new method for the observation of the same nannofossil specimens with scanning electron microscope and light microscope, involving the use of a grid, is described. This technique provides a complete analysis of the morphological diagnostic characteristics of calcareous nannofossils and other microfossils.